Indicadores operacionais dos hospitais universitários federais e o desempenho do ensino e pesquisa dos cursos de medicina - Viana, Walder Braga (2021)
Hospital management is an important subject and, as so, has been studied in its multiple dimensions. In addition to the high complexity, hospitals have to deal with the peculiarities and diversity of the services involved, which makes it even more difficult to control the management and the costs of their activities, especially in the case of university hospitals (HUs), whose mission is based on the tripod: care, teaching and research. In this perspective, the study aims to examine the relationship between the Brazilian Hospital Services Company (EBSERH) and the federal university hospitals (HUFs) operational performance and the teaching and research evaluation results of the Federal Universities. Additionally, the research aims to identify possible differences in HUFs operational performance indicators considering their size and location in the different regions of Brazil. The study is classified as descriptive in terms of objectives and quantitative in terms of means. The research was carried out using secondary data extracted from: the EBSERH Indicator Panel; the INEP-ENADE website, and the Scopus database. The analyzed sample was obtained from 38 HUFs under EBSERH Network management and refers to 2019 data. The following statistical techniques were applied: descriptive statistics, difference test between averages and correlation analysis. The results showed that the studied operational indicators did not present significant differences among the averages considering the Brazilian regions where the HUFs are located; However, considering to the size of the HUFs, there are significant differences among the averages, and it is possible to identify that: (i) the hospital occupancy rate, the renewal rate or turnover rate and the general operational performance indicator show higher averages in small hospitals and (ii) the number of consultations and number of surgeries showed higher averages in large hospitals. The obtained results allowed us to conclude that there is a positive and statistically significant correlation between the general operational performance of the HUFs, the ENADE score of medical courses linked to the HUFs, as well as with the medicine scientific production in the Scopus database. This study shows a general view of the EBSERH Network HUFs operational performance considering the care dimension and reveals its interrelationship with the teaching and research dimensions, indicating to public managers deficiencies that require more attention to improve hospital performance.